Newspaper and Journalistic Style in Modern Linguistics - Turg‘unova Fazilat Rustam qizi (Genius Publishing Group, 2023)
In newspapers and journalistic discourses, the basic principle of choosing language tools as a whole must be recognized as the evaluation of their pronunciation. All of this defines the relevance of studying all types of assessment tools, their nature and functions, methodological methods of incorporating them into texts of various genres, their sources of formation, reasons for updating, and the main trends in development. In modern linguistics, our article analyzes newspapers and journalistic styles based on what scientists have done.
Keywords: Title; journalist; newspaper; yang